THEORETICAL TESTING ON SERVICE QUALITY AND PRODUCT INNOVATION OF SMALL-MICRO CREDIT BANKS (A CASE STUDY) - Mohamad Dimyati (Universitas Hayam Wuruk Perbanas, 2011)
The research topic is a theoretic influence of service quality and product innovation on customerloyalty which are mediated by customer satisfaction and customer trust borrowing microand small scale credit of public bank in Jember Regency. The research examines the influencesof: service quality on customer satisfaction and customer trust as well as customerloyalty, customer satisfaction on customer loyalty, product innovation on customer trust andcustomer loyalty, customer trust on customer loyalty borrowing micro and small scale creditof public bank in Jember Regency. A purposive sampling with disproportional allocation on120 respondents was used to determine the sample (BRI, BNI, Bank Mandiri, and Bank Jatimbranch office Jember), employing the Structural Equation Modeling with AMOS Version 5.0.The results show that the service quality influences significantly the customer satisfactionand the customer trust as well as the customer loyalty with a positive relationship direction;The customer satisfaction and the product innovation influences significantly the customertrust with a positive relationship direction; The customer trust influence significantly the customerloyalty with a positive relationship direction. The customer satisfaction and the productinnovation do not influence the customer loyalty. The customer loyalty of the small andmicro debtors of the public banks in Jember Regency are direct influenced by the servicequality and the customer trust, and are indirectly influenced by the service quality, the customersatisfaction and the product innovation; the customer satisfaction and the productinnovation do not either directly nor significantly the customer loyalty.